2018
DOI: 10.14748/ssmd.v3i2.4332
|View full text |Cite
|
Sign up to set email alerts
|

The importance of upper first permanent molars position for the orthognatic occlusion

Abstract: Development of the dental arches and occlusion in permanent dentition can be divided into several stages and has to be observed regularly. The first permanent molar eruption is related to the onset of significant changes in the developing occlusion. Although this tooth is seen as the "key to occlusion" its value as an anchorage is debatable. The aim of the article is to study the correct position of the upper first molars in the two planes of spacethe sagittal and transverse planes. In this article the positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Dental neglect and stress levels can result in less salivary secretion leading to caries formation. Studies have shown that malondialdehyde levels are at a high level in saliva which increases the risk for development of ECC (World Health Organization WHO., 1997;McDonald and Sheiham, 1992;Taani and Quteish, 2004;Gurunathan and Shanmugaavel, 2016;Aishwarya and Gurunathan, 2017;Subramanyam et al, 2018;Ivanova et al, 2018;Krishnaswamy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental neglect and stress levels can result in less salivary secretion leading to caries formation. Studies have shown that malondialdehyde levels are at a high level in saliva which increases the risk for development of ECC (World Health Organization WHO., 1997;McDonald and Sheiham, 1992;Taani and Quteish, 2004;Gurunathan and Shanmugaavel, 2016;Aishwarya and Gurunathan, 2017;Subramanyam et al, 2018;Ivanova et al, 2018;Krishnaswamy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…occlusal caries was seen among young children and proximal caries among older children. Traumatic injuries can also result in fractured teeth and infections that can lead to caries formation (Edward, 1997;Lith et al, 2002;Hopcraft and Morgan, 2006;Christabel and Gurunathan, 2015;Packiri et al, 2017;Ravikumar et al, 2017;Ivanova et al, 2018;Krishnaswamy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%